Species Of The Family Trichogrammatidae And Their Biological Indicators - Kimsanbaev Khujjamurat; Kasimov Zafarbek; Jumaev Rasul (Zien Journals, 2025)
In the state a review of theoretical and practical work on the genus Trichogramma is presented. Analyzed bioecology, species composition and specialization of Trichogramma species on postpartum clopax.
Keywords: Trichogrammatidae; pintoi Voegele; T. principium Sug et Sor; T